The Development of Green Banking Theory - Risna Kartika; Herlina, Elin; Villanueva, Mima M. (Interdisciplinary International Journal of Conservation and Culture, 2023)
One of the complicated phenomena that has become a topic of discussion in various countries is climate change resulting from various human activities, one of which is business activity. This is the responsibility of all parties, including the economic sector with the banking finance sub-sector, so that the concept of green banking emerges which is a development of the concepts of green finance and green economy. This research aims to look at the development of green banking theory. The research method used in this research is a literature review. The results of the study show that the concept of green banking is seen from various aspects, including factors that influence it, namely environmental interests, stakeholder pressure, policy guidelines, economic factors, and requests for loan facilities. When viewed from consumer perceptions, green banking practices are quite well known by most people, however, there are still people who do not understand the existence of this green banking concept, so banks must contribute to educating customers about the importance of this. On the other hand, sustainability reports and sustainability development reports are also inseparable from this green banking concept, because completeness and consistency of reporting periods are a form of implementing green banking in banking which can increase corporate value. The banking sector, which is one of the main sources of financing for business activities, must consider the business activities it finances to contribute to environmental sustainability. This is in line with the issuance of regulations from the government that support the application of the green banking concept in various countries, including in Indonesia with the existence of POJK no 51/POJK.03/2017 concerning the application of the green banking concept carried out by banks in Indonesia with the aim of avoiding financing. for businesses that have the potential to damage the environment, social and governance, this is related to the policy of providing banking credit facilities which requires an Environmental Impact Assessment.